Sombor Index, Randic Index, and Forgotten Index of Fuzzy Coprime Graph on Dihedral Group - Gusti Yogananda Karang; I Gede Adhitya Wisnu Wardhana; Ni Wayan Switrayni (InPrime: Indonesian Journal of Pure and Applied Mathematics, 2026)
This research investigates the topological indices—Sombor, Randic, and Forgotten—of the fuzzy coprime graph constructed from dihedral groups. These indices, which quantify graph structural properties, have important applications in mathematical chemistry and algebraic graph theory. The study begins by defining fuzzy graphs and coprime graphs, and then introduces the fuzzy coprime graph as a combination of both. Focusing on the dihedral group D_{2n}, with n=p where p is an odd prime, the paper classifies vertices and edges based on their membership values and determines the degree of each vertex. Using these classifications, general formulas for each index are derived. The results show that the fuzzy prime-coprime graph of the dihedral group forms a complete tripartite graph, enabling explicit computation of the Sombor index, Randic index, and Forgotten index. This work extends previous studies by integrating fuzziness into group-based graph representations, offering a new approach to analyzing algebraic structures through topological indices. The findings provide a foundation for future exploration of fuzzy algebraic graphs and their applications in mathematical modeling. AbstrakPenelitian ini menyelidiki indeks topologis—Sombor, Randić, dan Forgotten—pada graf koprima fuzzy yang dibangun dari grup dihedral. Indeks-indeks ini, yang mengukur properti struktural graf, memiliki aplikasi penting dalam kimia matematika dan teori graf aljabar.Studi ini dimulai dengan mendefinisikan graf fuzzy dan graf koprima, kemudian memperkenalkan graf koprima fuzzy sebagai kombinasi keduanya. Dengan fokus pada grup dihedral D_{2n}, dengan n=p dengan p adalah bilangan prima ganjil), penelitian mengklasifikasikan simpul dan sisi berdasarkan nilai keanggotaannya serta menentukan derajat setiap simpul. Berdasarkan klasifikasi ini, rumus umum untuk setiap indeks diturunkan Hasil penelitian menunjukkan bahwa graf koprima fuzzy dari grup dihedral membentuk struktur graf tripartit lengkap, sehingga memungkinkan perhitungan eksplisit untuk indeks Sombor, indeks Randic, dan indeks Forgotten. Karya ini memperluas penelitian sebelumnya dengan mengintegrasikan konsep fuzziness ke dalam representasi graf berbasis grup, menawarkan pendekatan baru untuk menganalisis struktur aljabar melalui indeks topologis. Temuan ini memberikan dasar untuk eksplorasi lebih lanjut mengenai graf aljabar fuzzy dan aplikasinya dalam pemodelan matematika.Kata Kunci: Graf fuzzy; Grup dihedral; Graf koprima; Indeks Sombor; Indeks Randic; Indeks Forgotten. 2020MSC: 05C22, 05C09.